The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1016/j.molonc.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits tumor proliferation induced by neutrophil elastase through the upregulation of α1‐antitrypsin in lung cancer

Abstract: A B S T R A C TLung carcinogenesis is a complex process in an unregulated inflammatory environment.Curcumin has been extensively investigated as a multi-target anti-tumor and antiinflammation compound. In this paper, we demonstrate a novel inflammation-related mechanism for curcumin-induced inhibition of lung tumor growth. We found that neutrophil elastase, an important regulator of inflammatory processes, directly triggered tumor cell proliferation in human lung adenocarcinoma A549 cells, and curcumin could c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…In tumor tissues of mice treated with curcumin, there was upregulation of α1-antitrypsin and decrease in the protein level of neutrophil elastase which play important roles in modulating lung tumor proliferation in inflammatory microenvironment. This study highlighted a new inflammation-related mechanism of curcumin against tumor proliferation and advocates the possible role of curcumin in the treatment of other inflammation-related diseases in lung such as emphysema [69]. Decrease in tumor growth and increase in survival contributed to T cell-mediated adaptive immune response was found in tumor-bearing mice treated with low-dose curcumin (50 mg/kg body weight) for ten days.…”
Section: Curcumin and Lung Cancermentioning
confidence: 98%
“…In tumor tissues of mice treated with curcumin, there was upregulation of α1-antitrypsin and decrease in the protein level of neutrophil elastase which play important roles in modulating lung tumor proliferation in inflammatory microenvironment. This study highlighted a new inflammation-related mechanism of curcumin against tumor proliferation and advocates the possible role of curcumin in the treatment of other inflammation-related diseases in lung such as emphysema [69]. Decrease in tumor growth and increase in survival contributed to T cell-mediated adaptive immune response was found in tumor-bearing mice treated with low-dose curcumin (50 mg/kg body weight) for ten days.…”
Section: Curcumin and Lung Cancermentioning
confidence: 98%
“…These properties have been heavily assessed for exploring its potential utilization in cancer treatment [28,29] . In addition, a few recent studies have reported the potential effect of curcumin in promoting white adipocyte "browning" [30,31] .…”
Section: Dietary Polyphenol and Dietary Polyphenol Interventionmentioning
confidence: 99%
“…Lung cancer accounts for about 18 % (1.4 million) of the death in 2008 [8] and estimated 28 % of the death in 2012 [9]. Recent studies highlighted that chronic inflammation is critical and dependent in the complex process of lung carcinogenesis [10]. Local infections (e.g., viral infections, pneumonia, or tuberculosis) and inflammation often occur in patients with lung cancer [11].…”
Section: Introductionmentioning
confidence: 99%